2017
DOI: 10.5693/djo.02.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser–assisted cataract surgery in vitrectomized eye with posterior chamber phakic intraocular lens

Abstract: SummaryWe describe a case of femtosecond laser-assisted cataract surgery (FLACS) in an eye with multiple comorbidities, including retinal detachment surgery, high myopia, posterior chamber phakic intraocular lens (PC pIOL) and residual, emulsified, silicone oil located in the anterior chamber. FLACS was affected by the optical blockage, but the incomplete capsular tear was recoverable. The case suggests that silicone oil bubbles concentrated at the dome of the posterior corneal surface, along with the PC pIOL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Several authors have described the use of FLACS in eyes with anterior and posterior chamber ICLs. [345678] Anisimova et al reported bubbles similar to ours which lead to incomplete capsulotomy but did not interfere with nuclear fragmentation. [4] Similarly, Kaur et al reported incomplete nucleotomy due to bubble entrapment.…”
Section: Discussionsupporting
confidence: 76%
“…Several authors have described the use of FLACS in eyes with anterior and posterior chamber ICLs. [345678] Anisimova et al reported bubbles similar to ours which lead to incomplete capsulotomy but did not interfere with nuclear fragmentation. [4] Similarly, Kaur et al reported incomplete nucleotomy due to bubble entrapment.…”
Section: Discussionsupporting
confidence: 76%